(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Neck and arm pain is common in the general population.1,2 Individuals with neck and upper extremity symptoms demonstrate greater levels of disability than do individuals with neck pain alone.3 While individuals with cervical radiculopathy often report neck pain, they most frequently seek treatment due to arm pain.3–5 Individuals with whiplash associated disorders who demonstrate signs of irritation of the brachial plexus and subsequent neck and arm pain reported more severe symptoms and achieved worse outcomes than those without brachial plexus irritation.6 Some authors have suggested that patients with neck and arm pain should be treated more expeditiously in order to avoid the further negative impact on mental health status associated with chronic symptoms.